Phase transitions in bulk and confined organic ferroelectric DIPAI - A.Yu. Milinskiy; S.V. Baryshnikov; E.V. Charnaya; I.V. Egorova; V.M. Sarnatskii (Results in Physics, 2020)
We studied phase transitions in new organic ferroelectric DIPAI embedded into porous alumina and in bulk DIPAI. Complex permittivity and third harmonic generation coefficient were measured within a wide temperature range. The increase in the third harmonic generation indicates the emergence of the polar phase. Two phase transitions were seen in bulk DIPAI upon heating from room temperature after preliminary heating up to 420 K while only a transition was found upon cooling accompanied with pronounced thermal hysteresis. The ferroelectric phase was observed in the range between two transitions upon heating and below the transition upon cooling. In contrast, two phase transitions occur in DIPAI confined to porous alumina upon heating and cooling. The transitions do not show noticeable thermal hysteresis. It was suggested that different behavior of bulk and confined DIPAI results from slow kinetics of phase transitions in bulk upon cooling. The noticeable shift of the transition temperatures for DIPAI within alumina pores of different diameters was treated using the theories of size effects in ferroelectrics.